Application of proactive planning for optimizing the recruitment process of bKash Limited: a study on enhancing effectiveness - Tasneem, Promity (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.